Screening of organophosphate esters in different indoor environments: Distribution, diffusion, and risk assessment. (15th June 2023) - Jia, Tianqi; Gao, Lirong; Liu, Wenbin; Guo, Bobo; He, Yunchen; Xu, Xiaotian; Mao, Tianao; Deng, Jinglin; Li, Da; Tao, Fang; Wang, Wenwen
Abstract: Analysis: of air conditioner (AC) filter dust can reveal the level of organophosphate ester (OPE) pollution in indoor environments, but comprehensive research on this topic remains lacking. This study combined non-targeted and targeted analysis to screen and analyze 101 samples of AC filter dust, settled dust, and air obtained in 6 indoor environments. Phosphorus-containing organic compounds account for a large proportion of the organic compounds found in indoor environments, and OPEs might be the main pollutants. Using toxicity data and traditional priority polycyclic aromatic hydrocarbons for toxicity prediction of OPEs, 11 OPEs were prioritized for further quantitative analysis. The concentration of OPEs in AC filter dust was highest, followed in descending order by that in settled dust and that in air. The concentration of OPEs in AC filter dust in the residence was two to seven times greater than that in the other indoor environments. More than 56% of the OPEs in AC filter dust showed significant correlation, while those in settled dust and air were weakly correlated, suggesting that large amounts of OPEs collected over long periods could have a common source. Fugacity results showed that OPEs were transferred easily from dust to air, and that dust was the main source of OPEs. The values of both the carcinogenic risk and the hazard index were lower than the corresponding theoretical risk thresholds, indicating low risk to residents through exposure to OPEs in indoor environments. However, it is necessary to remove AC filter dust in a timely manner to prevent it becoming a pollution sink of OPEs that could be rereleased and endanger human health. This study has important implications for comprehensive understanding of the distribution, toxicity, sources, and risks of OPEs in indoor environments. Graphical abstract: Image 1 Highlights: Organophosphates Esters (OPEs) in filter dust were higher than those in settled dust. Twenty-one OPEs were screened and 11 of them were selected as priority pollutants. Interior decoration and furniture are the potential main sources of OPEs. The fugacity indicated that OPEs were easily transferred from dust to air. Air conditioner dust becomes a sink for OPEs and needs to be cleaned regularly.